VAMP2 is a cerebrospinal fluid marker of selective hippocampal synapse loss and episodic memory performance in Alzheimer's disease: Biomarkers (non‐neuroimaging) / Multi‐modal comparisons. (7th December 2020) - Belbin, Olivia; Molina, Beatriu; Núñez‐Llaves, Raúl; Goossens, Julie; Dewit, Nele; Alcolea, Daniel; Estellés, Teresa; Querol‐Vilaseca, Marta; Dolcet, Sonia Sirisi; Muñoz, Laia; Clarimon, Jordi; Blesa, Rafael; et al.
Abstract: Background: An early objective cerebrospinal fluid (CSF) marker of cognitive decline in preclinical Alzheimer's disease (AD) would be a useful addition to the current AD biomarker arsenal. We recently identified VAMP2 as a potential CSF marker of AD‐related synapse loss. The aim of this study was 1) to evaluate the regional brain expression of VAMP2 in human postmortem tissue and 2) to assess the correlation of CSF VAMP2 levels with cognitive performance in cognitively normal controls and AD patients. Method: Paraffin fixed brain sections from hippocampus, frontal, posterior‐cingulate and temporal inferior cortices from AD cases (n=10) and non‐pathological controls (n=10) were stained with anti‐VAMP2 (Cell Signaling) and an HRP‐conjugated (Dako) secondary antibody. VAMP2 was quantified using MATLAB software (MA, USA). CSF from the Sant Pau Initiative in Neurodegeneration (SPIN) cohort was selected from cognitively normal controls (n=68), preclinical AD stages 1 (n=31) and 2 (n=8), prodromal AD (n=80) and AD dementia patients (n=39). Cognitive performance was evaluated using the total score in the Free and Cued Selective Reminding Test (Buschke et al). We quantified VAMP2 in CSF by Single MOlecule Array (SIMOA). Result: In control and AD brains, VAMP2 showed a neuropil‐like expression pattern consistent with a synapse marker and was widely expressed in cortical and subcortical regions (hippocampus>frontal cortex>cingulate cortex>temporal cortex). VAMP2 expression in AD brains was reduced 0.6‐fold compared to controls in the hippocampus (p=0.01) but comparable to controls in all other regions tested (all p>0.1). Reduced hippocampal VAMP2 levels correlated with increased Braak (r 2 =0.4, p=0.006) and CERAD (r 2 =0.3, p=0.03) staging. In CSF, VAMP2 levels were decreased compared to controls in preclinical AD and sequentially elevated over the course of AD, plateauing at the prodromal stage. Worse episodic memory was associated with increased CSF VAMP2 in controls (r 2 =0.09, p=0.009). In AD, the best fit was a nonlinear model (r 2 =0.07, p=0.0009) in which worse episodic memory was associated with increased CSF VAMP2 in preclinical AD but decreased VAMP2 in clinical AD. Conclusion: These data support VAMP2 as a promising CSF marker of selective hippocampal synapse loss and episodic memory performance in Alzheimer's disease and healthy controls.